2017
DOI: 10.1016/j.fitote.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic and biosynthetic relationships between flavonolignans produced by Silybum marianum populations

Abstract: Flavonolignans constitute an important class of plant secondary metabolites formed by oxidative coupling of one flavonoid and one phenylpropanoid moiety. The standardized flavonolignan-rich extract prepared from the fruits of Silybum marianum is known as silymarin and has long been used medicinally, prominently as an antihepatotoxic and as a chemopreventive agent. Principal component analysis of the variation in flavonolignan content in S. marianum samples collected from different locations in Egypt revealed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Silymarin is reportedly produced via the oxidative coupling of two major precursors, namely, taxifolin and coniferyl alcohol [21]. Most major enzymes responsible to produce both taxifolin and coniferyl alcohol were present in our transcriptome data (Supplementary Table 2), which is consistent with other medicinal plants observed in the same family [6, 20]. In the C. japonicum transcriptome assembly, we identified silymarin biosynthesis-related unigenes (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Silymarin is reportedly produced via the oxidative coupling of two major precursors, namely, taxifolin and coniferyl alcohol [21]. Most major enzymes responsible to produce both taxifolin and coniferyl alcohol were present in our transcriptome data (Supplementary Table 2), which is consistent with other medicinal plants observed in the same family [6, 20]. In the C. japonicum transcriptome assembly, we identified silymarin biosynthesis-related unigenes (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Silymarins are the major flavolignans produced in C. japonicum . Taxifolin and coniferyl alcohol are the two major precursors responsible for the production of silymarin [20] and are produced by the flavonoid and phenylpropanoid pathways, respectively, as shown in Fig. 5 (the highlighted boxes represent the enzymes annotated in our data).…”
Section: Resultsmentioning
confidence: 99%
“…With such a mechanism, only equimolar mixtures silybin (A and B) and isosilybin (A and B) diasteroisomers are supposed to be produced. However, some authors have reported different molar ratios [ 31 , 51 , 58 , 59 ]. Recently, Martinelli et al [ 53 ] suggested the possible involvement of dirigent-like proteins that could explain such a discrepancy.…”
Section: Resultsmentioning
confidence: 99%
“…The methanolic extract of Milk Thistle ( Sylibum marianum L. Gaertner), called silymarin, is a mixture of at least 8 flavolignans [ 110 ], from which Silybins A and B are among the major compounds ( C8 ) [ 111 ]. The oral bioavailability of silymarin flavolignans is relatively low, mainly due to their poor intestinal resorption, low aqueous solubility, high hepatic first-pass effect and rapid excretion in bile and urine [ 112 ].…”
Section: Future Direction For the Management Of The Diseasementioning
confidence: 99%